Novel solid biopolymer electrolyte based on methyl cellulose with enhanced ion transport properties. Issue 12 (30th October 2021) - Koliyoor, Jayalakshmi; Ismayil,; Hegde, Shreedatta; Vasachar, Ravindrachary; Sanjeev, Ganesh
Abstract: Magnesium ion conducting solid polymer electrolyte films are prepared with biodegradable methyl cellulose and Mg(NO3 )2 .6H2 O by solution casting method. FTIR spectrum of the films confirmed the interaction between the polymer host and the metal salt. FTIR deconvolution gives a clear picture of the percentage of free ions with the salt concentration variation. Structural modification of the polymer upon salt doping are studied with XRD analysis. Glass transition temperature of the pristine film is found to increase with the concentration of the salt, which is attributed to an increase in the coordination between Mg +2 and oxygen atoms of the polymer matrix and formation of transient crosslinks. TGA analysis accounts for the thermal stability of the electrolyte films. The electrical properties of the films have been analyzed, and the values of ionic conductivities of the films were calculated. Electrolyte film with 25 wt% of the salt, which is highly amorphous, is found to have the highest room‐temperature ionic conductivity of 1.02 × 10 −4  S cm −1 . SEM micrographs show variation in the surface morphology of the electrolytes with the variation in the concentration of the salt. The films' electrochemical stability window and ionic transference number are calculated to find the suitability for energy storage applications. Abstract :